That's not what I meant! a qualitative study on the Filipina's indirectness in asking for what she wants in conflict arousal and resolution stages within a boyfriend-girlfriend relationship - Cordova, Jennifer B. 1977-
This thesis entitled "THAT'S NOT WHAT I MEANT! : A Filipina's indirect way of stating what she wants in boyfriend-girlfriend relationship in a conflict resolution situation" is qualitative in nature. Its aim to provide reasons for girl indirectness during conflict arousal and resolution stages. Aside from this, also included in the study are the different perceptions of males and females regarding indirectness, instances and indicators of indirectness and effectiveness and effects of indirectness. Furthermore, the role of culture and gender in the act of being indirect is also emphasized. To achieve this, the researcher used four qualitative methods to provide justifications to the research objectives. The first method is Focus Group Discussion. This establishes general patterns regarding the act of indirectness. Focus interviews are used to support the findings from the Focus Group Discussion and provide specific accounts from the interviewees. Thirdly, Participant Observation is used to verify the findings of the previous methods through observation. Finally, key informants are used to support the findings with psychological, anthropological and communicational explanations. The study is guided by five theories. Each theory has a corresponding concept or aspect of indirectness to explain. The Semiotic and Dissonance theory is used to interpret the verbal and nonverbal cues exchanged during the process of communication. This explains the existence of conflicts because when the verbal and nonverbal do not complement each other, it leads to fights. Also, couples also have a difficulty in understanding what each one is saying due to different cultural orientations and different attributions. The theory Meanings of meanings is used to determine the meaning of the signs and signals within the communication context. Finally, the Speech Code theory and Coordinated Management of Meaning Theory explains the role of language, culture Filipino values and gender differences in affecting the indirect trait of women. The integration of all the theories provides a holistic explanation of the processes and elements involving indirectness and indirectness as a whole. With the data gathered and careful interpretation arising therefrom, the study concludes that indirectness is an act performed with a purpose, at a particular scene with individuals acting as agents for the delivery of indirect messages. It is the blurring of the real pursuit of what really wants. It has become a tool for coping with the potentially embarrassing or hurtful situations having Filipino values to govern it. This includes "hiya," "pakikiramdam," "amor propio" and utang na loob." The act of indirectness employs contradicting verbal and nonverbal cues to come up with the indirect message. There are many reasons influencing indirectness. These reasons can be categorized into situational and societal reasons. Situational reasons include the instances in the relationship that makes one become indirect. These reasons only appear during the scenario preceding indirectness. It determines effectiveness or ineffectiveness of indirectness. Environmental, historical, psychological reasons affect an individual's pursuit of indirectness. In addition to this, the pursuit of indirectness is an individual choice. Finally, the effectiveness of indirectness depends on the people involved in the relationship. It also depends on the situation and manner of delivery. There are instances when indirectness is effective but there are instances when it is ineffective.